Sociocultural and Anthropoecological Distinctive Features of Pedagogical Discourse - Maksim V. Kochetkov (Publishing house "Sreda", 2020)
The relevance of the study is due to the complexity of socio-cultural reality due to the aggravation of the contradiction between globalization and national-oriented processes, the increasing struggle of cultures, economies and ideologies, and the acceleration of scientific and technological progress. The purpose of the article is to consider sociocultural and anthropoecological distinctive features of pedagogical discourse. The author points out that anthropo-innovations, such as genetic engineering, cyborgization, cloning, integration with artificial intelligence, pharmaceutical advances, and GMO products threaten the existence of a person in his or her mental and physical integrity. The restriction of anthropological innovations is due to spiritual revival, reliance on traditional cultures, as well as the best cultural and pedagogical national experience, and is determined by the understanding of the soul as an integrating component of a person. In the Humanities, the description of an increasingly complex socio-cultural reality is closely related to its description in the context of various discursive plans. This approach is also promising for pedagogy. At the same time, modern trends in the development of the discursive approach "blur" the boundaries of pedagogical knowledge. The article presents a highly specialized definition of pedagogical discourse. During the study the following methods were applied: analysis of legal documents and scientific and methodical literature. It is proved that the pedagogical category "zone of proximal development" in its socio-cultural and anthropo-ecological contexts favors understanding of the distinctive features of educational and pedagogical discourse. It is concluded that orientation to the zone of proximal development of the individual contributes to the consistency of the socio-cultural experience, including nationally oriented components, transmitted by the teacher, with the life experience of the student, favors his or her emotional involvement in the educational process.